Tamaños y frecuencia de Pontonia margarita(Crustacea: Palaemonidae) asociada a Pinctada mazatlanica (Bivaivia: Pteriidae), Costa Rica - Cabrera Peña, Jorge (Universidad de Costa Rica, 1996)
Size and frecuency observations of Pontonia margarita (Smith 1869) from the paleal cavity of Pinctada mazatlanica (Hanley 1956), were made from March to August 1993. The caparace length af P. margarita was 4.00- 15.25 mm, and 2.75-11.00 mm for females and males, respectively. Ovigerous females were found in all months with highest percentages in April and July (83.3 and 100 % respectively). The relationships caparace length-weight were w= 1.330 x 10-' LC'"'' for males and W= 2.060 x 10-3 LC2.509 for females. The mean sex-ratio was 1.0 male : 1.15 females.